Analisis Dampak Media Digital terhadap Persepsi Identitas Nasional di Kalangan Remaja (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the impact of digital media on perceptions of national identity among teenagers. In the midst of globalization and technological advances, digital media—especially social media—plays a significant role in shaping teenagers' views and information behavior, including their understanding of national identity. Through a qualitative approach involving in-depth interviews and content analysis from various digital platforms, this research identifies how digital media both strengthens and changes teenagers' perceptions of cultural and national values. The findings show that digital media can be a positive channel for introducing local and national cultural riches, but it also carries the risk of